The Environmental Impact of Trade Openness on CO2 Emissions: Empirical Evidence from Somalia - Abdulle, Abdikani Yusuf; Mohamed, Idiris Sid Ali (International Journal of Energy Economics and Policy, 2024)
This research examines the effects of trade openness on carbon emissions in Somalia from 1980 to 2021. Somalia’s economy is strongly dependent on exporting goods including cattle, charcoal, and raw agricultural products, which contribute to high carbon emissions. The study employed Autoregressive Distributed Lag (ARDL), full modified Ordinary Least Squares (FMOLS), dynamic Ordinary Least Squares (DOLS), and Canonical Co-integrating Regression (CCR) to analyze the immediate and long-term correlation between trade openness and carbon dioxide emissions in Somalia. When there are different types of variables, our approach, which includes the ADF unit root test, verifies that all variables show first-order integration (I (1)) and stationary behavior (I (0)). The ARDL-bound tests for co-integration reveal a durable connection between carbon emissions and several factors, including trade openness, gross domestic product (GDP), foreign direct investment (FDI), and population increase. The findings demonstrate a statistically significant and inverse relationship between trade openness and short-term carbon dioxide emissions. The heightened levels of trade openness have a noticeable detrimental effect on carbon emissions. Furthermore, there is a strong and statistically significant negative relationship between energy consumption, RGDP, and population increase with carbon emissions, except for RGDP which shows no significant impact. FDI exhibits a robust and meaningful correlation with carbon emissions in both the short and long term. In addition, Somalia’s population is experiencing significant growth, making it one of the fastest-growing populations in the world. This growth leads to an increased demand for energy, land, and consumption, which in turn contributes to higher emissions. However, the research did not take into account other possible factors that could have an impact, such as technical advancements, global economic changes, climate change, and policy adjustments. The report advised that future research explore the possibilities of sustainable trade practices, improvements in energy efficiency, and the use of renewable energy as means to minimize CO2 emissions.